Kajian Pemikiran Dakwah dan Komunikasi Hasan Basri - Muslimin Muslimin; Zenal Arifin (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2019)
This study wants to find out how Hasan Basri's preaching and communication thoughts. Then this study also wanted to find out how the preaching and communication activities of Hasan Basri. Through this research benefits will be obtained. First, to obtain information, data, and biography about Hasan Basri in preaching and communication thinking. Second, gaining knowledge about the preaching and communication thoughts of Hasan Basri. This research can be concluded, first, the ideas and thoughts of Hasan Basari's preaching tend to be Sufism. While the communication patterns developed by Hasan Basri lead to an invitation to be zuhud, it is important for someone to develop good intrapersonal communication. Including also avoiding communication messages that sounded ghibah.